Medicalization of the educational process: Stating the problem - Gumarova, Anastasia Nikolaevna (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2023)
Introduction. The spread of medical theories and practices to various spheres of society is becoming a significant factor in the development of society. In the scientific literature this phenomenon is called medicalization. The essence, causes and consequences of medicalization are comprehended in philosophical and bioethical discourses. Medicalized practices are also being introduced into the process of education. Theoretical analysis. Consideration of the problem made it possible to reveal that pedagogical means of solving the problems of education are supplemented or replaced by means of medical influence on the human body. The features of students’ behavior are marked as symptoms of neuropsychiatric diseases that require treatment. Correction of students’ behavior with the help of medical means is associated with the disciplinary nature of education, considered in the biopolitical concept of M. Foucault. The transformation of the cultural understanding of the norm under the influence of natural science theory stands out as a trend of the development of modern science, contributing to the growth of medicalization. Also, the development of the biological concept of psychiatry and the achievements of neuroscience contribute to the medicalization of the process of education. Conclusion. The medicalization of the process of education is followed by new social risks that have philosophical, methodological, social, humanitarian and ethical grounds. It is concluded that it is necessary to conduct a social and humanitarian examination of medicalized educational practices and analyze the compliance of medicalized practices with the goals and objectives of education.